Improving Mental Health of Adolescents through Self-Presentation - Ferina Agustia Yuarta; Ira Nurmala (Institute of Medico-legal Publications Pvt Ltd, 2021)
Mental health is currently the problem faced by youth especially during the pandemic of COVID-19.Adolescents use of social media is also increasing due to this coronavirus pandemic. This situation have riskof increasing the risk of lower mental health of Adolescent as the impact of posting their self-presentationthrough a social media such as Instagram. Instagram is a social media platform that has a rapid user growth.Indonesia is one of the countries with highest number of users. Instagram users recorded as of May 2020had reached 9.2 million users. Instagram as social media is a means for users to present themselves towide audience. Self-presentation can be in the form posting photos or videos on their Instagram socialmedia accounts. By posting photos, user hope to get feedback in the form of likes and comments. Thisresearch aims at the improving mental health of adolescent through self-presentation. This research usedis secondary data obtained from journal database. The sample was 35 scientific articles obtained from thebasis of screening journal that has been screened using pre determine inclusion criteria. The result found thatself-presentation on social media Instagram was related to giving or managing impression, popular, selfdisclosure, narcissistic behavior, self-image and self-esteem that in turn will result in lowering adolescentmental health if it is not manage well.